GAMBARAN AKTIVASI SISTEM IMUN IKAN NILA (Oreochromis niloticus) TERHADAP PEMBERIAN DAUN SANGKAREHO (Callicarpa longifolia Lam.) MELALUI PAKAN - Maryani Maryani; Muhammad Rozik; Nursiah Nursiah; Asri Pudjirahaju (Universitas Batangahari Jambi, 2021)
One way to improve the quality of the seed from cultured fish is to increase the immune response so that it is immune to disease attacks. This study aims to increase the non-specific immune response of tilapia by giving the optimum dose of sangkareho leaf extract. The treatment given was the difference in the dose of the leaf extract, where the difference in the dose was as follows: A = dose 0 gr/kg feed, B = dose 5 gr/kg feed, C = dose 10 gr/kg feed, D = dose 15 gr /kg of feed, and E = dose of 20 g/kg of feed. The main parameters observed were the examination of the number of Hb, He, erythrocytes, leukocytes, and survival rate (SR). Blood sampling during the study was carried out on the 16th day after being given the extract of the sangkareho leaf, and infected with A. hydrophila bacteria. The results showed that the use of the extract of the bay leaf as an immunostimulant affected the number of Hb, He, erythrocytes, leukocytes, and the survival rate of tilapia infected by Aeromonas hydropila.